Nutritional Composition of Ten Persimmon Cultivars in the “Ready-to-Eat Crisp” Stage. Effect of Deastringency Treatment - Novillo, Pedro; Besada, Cristina; Tian, Li; Bermejo, Almudena; Salvador, Alejandra (SCIRP, 2020)
Traditionally persimmons have been consumed over-ripened to avoid astringency perception. However, the introduction of new technology that removes astringency while preserving fruit firmness has allowed the commercialization of “ready-to-eat crisp” fruits. Several studies have evaluated the nutritional composition of over-ripened persimmons and have claimed that they are a good source of primary and secondary metabolites that are favourable for human health. Yet very little is known about the nutritional composition of persimmons in the “ready-to-eat crisp” stage. In this context, we determined the main nutritional compounds in ten popular persimmon cultivars, including astringent cultivars (“Rojo Brillante”, “Tone Wase”, “Giboshi”, “Kaki Tipo”, “Aizumishirazu-A”, “Giombo”, “Hachiya”) and non-astringent cultivars (“O’gosho”, “Hana Fuyu” and “Jiro”). To this end, fruits were harvested when their texture was firm, and soluble polyphenols content, total antioxidant capacity and main sugars, organic acids and carotenoids were evaluated. In those astringent cultivars at harvest, the changes in nutritional compounds associated with applying deastringency treatment with high CO2 concentration were determined. Our results revealed the main sugars (glucose, fructose and sucrose), organic acids (citric acid, malic acid and succinic) and carotenoids (β-cryptoxanthin, lutein, violoxanthin, zeaxanthin, and β-carotene) present in the flesh of crisp persimmons. At harvest the content of these metabolites vastly varied among cultivars; astringent cultivars showed higher soluble polyphenols and greater antioxidant capacity, and presented higher contents of sugars and organic acids than non-astringent ones. The deastringency treatment applied to astringent cultivars resulted in a drastic loss of soluble polyphenols and total antioxidant capacity, and induced changes in carotenoids and sugars composition.